NPK Fertilizer With Slow Release Fly Ash - Nadhira Izzatur Silmi; Fidela Azaria Antasari; Della Afriyana; Ridha Dini Rahmawati; Ilham Sidik; Sri Wardhani (Chemistry Department, The University of Brawijaya, 2018)
Fly ash is the solid of the remaining coal combustion carried along with the exhaust gas and captured by the air controller. Fluids in fly ash are Al2O3, SiO2, Fe2O3, CaO, MgO, Na2, and SO3 which are similar to zeolites. So that fly ash can be used as a substitute for zeolite for various carrier of fertilizer. The result of slow release test is known that N element has higher release level. The NPK fertilizer activity test of Fly Ash Slow Release was done on chilli plant with parameter of variation of fertilizer composition and plant height. Based on research result, fly ash-TSP 2: 1 fertilizer has the best result.